2007
DOI: 10.1097/mpa.0b013e31811f4526
|View full text |Cite
|
Sign up to set email alerts
|

The Integrin-Extracellular Matrix Axis in Pancreatic Cancer

Abstract: Pancreatic cancer is the fifth leading cause of adult cancer death in the United States, with 5-year survival rates of only 1% to 4%. Current therapeutic strategies generally result in only a few months of extended life. Recent evidence from several independent laboratories in vitro and in vivo indicate that integrin-mediated cell attachment to the extracellular matrix (ECM), components of which are highly up-regulated in pancreatic cancer, evokes phenotypes and signaling pathways that regulate tumor cell grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
98
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 76 publications
7
98
0
1
Order By: Relevance
“…The tumors develop a dense collagen-rich extracellular matrix [26], consistent with the observation that collagen I is up-regulated in human PDAC [34]. In BxPC-3 and Capan-2 tumors, the collagen fibers appear in thick filament bundles, whereas in MIAPaCa-2 and Panc-1 tumors, the collagen is seen as a dense network of thin fibers surrounding single tumor cells [26].…”
Section: Discussionsupporting
confidence: 62%
“…The tumors develop a dense collagen-rich extracellular matrix [26], consistent with the observation that collagen I is up-regulated in human PDAC [34]. In BxPC-3 and Capan-2 tumors, the collagen fibers appear in thick filament bundles, whereas in MIAPaCa-2 and Panc-1 tumors, the collagen is seen as a dense network of thin fibers surrounding single tumor cells [26].…”
Section: Discussionsupporting
confidence: 62%
“…43,44 only the expression of the a 1 b 1 and a 2 b 1 integrins has been examined in pancreatic adenocarcinoma so far. 25 Results from these previous studies indicate that both the a 1 b 1 and a 2 b 1 integrins are expressed in vivo at both the mRNA and protein levels in pancreatic cancer. In vitro, a 2 b 1 integrin expression has been shown in 18/19 cell lines (95%), while a 1 b 1 integrin expression has been demonstrated in 7/13 cell lines (54%).…”
Section: Discussionmentioning
confidence: 99%
“…3,4,[6][7][8][9][10][11] These cations presumably exert their effects by binding to the 3-5 putative cation-binding domains located on all integrin a subunits, 12 and possibly by interacting directly with b subunits. 13 We have recently demonstrated that a 2 b 1 integrin-mediated pancreatic cancer cell adhesion to Type I collagen, an ECM protein shown to be highly upregulated in pancreatic cancer [14][15][16][17] and to promote the malignant phenotype in vitro and in vivo, [18][19][20][21][22][23][24][25] is promoted in 1.5 mM Mg 21 and inhibited in 1.5 mM Ca 21 , 21 and that the a 2 b 1 integrin from pancreatic cancer cell lysates bound specifically to Type I collagen by affinity chromatography in 3 mM Mg 21 , can be eluted with 3 mM Ca. 2126 These data are consistent with our previous observations regarding the a 2 b 1 integrin, Type I collagen, and the various cell types involved in cutaneous wound repair, [27][28][29] of which strong parallels to the pancreatic cancer paradigm have been described.…”
mentioning
confidence: 99%
“…Secreted by CAFs, these stromal elements not only provide structural support but are also involved in differentiation, remodeling and carcinogenesis. Collagen I was shown to promote gemcitabine resistance in vitro (22,23). It also interacted with collagen IV and integrins on the surface of PDA cancer cells, and is vital for proliferation, maintenance of migratory phenotype, and avoiding apoptosis (24).…”
Section: Acellular Extracellular Matrix (Ecm)mentioning
confidence: 99%